1992
DOI: 10.1093/infdis/166.6.1429
|View full text |Cite
|
Sign up to set email alerts
|

Cholera in Piura, Peru: A Modern Urban Epidemic

Abstract: In late January 1991, epidemic cholera appeared in Peru. Within 2 months, 7922 cases and 17 deaths occurred in Piura, a Peruvian city of 361,868. A hospital-based culture survey showed that 79%-86% of diarrhea cases were cholera. High vibriocidal antibody titers were detected in 34% of the asymptomatic population. A study of 50 case-patients and 100 matched controls demonstrated that cholera was associated with drinking unboiled water (odds ratio [OR], 3.9; 95% confidence interval [CI], 1.7-8.9), drinking beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 11 publications
0
67
0
3
Order By: Relevance
“…Such contamination could easily overwhelm the chlorine. Studies in Peru and Calcutta have suggested that boiling water before drinking and storing water in a narrow-mouthed, capped container decreases the risk of cholera transmission [7,8,[17][18][19]. Our investigation did not document the type of container used to store boiled water, but having boiled water in the house at the time of inspection was protective.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Such contamination could easily overwhelm the chlorine. Studies in Peru and Calcutta have suggested that boiling water before drinking and storing water in a narrow-mouthed, capped container decreases the risk of cholera transmission [7,8,[17][18][19]. Our investigation did not document the type of container used to store boiled water, but having boiled water in the house at the time of inspection was protective.…”
Section: Discussionmentioning
confidence: 73%
“…Public health officials had to decide on preventive measures based on knowledge of how cholera spread in previous epidemics and on anecdotal information. This investigation and parallel investigations in Peru provided the first information from controlled studies about the most important modes and vehicles of transmission for cholera in Latin America [7][8][9]. Identification of specific modes of cholera transmission allows control measures and education to be more focused and, presumably, more effective.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Começaram a aparecer novos poços em zonas de alta concentração de latrinas e sem nenhuma medida de proteção. Apesar de não ter sido possível realizar investigações epidemiológicas que ajudassem a identificar os fatores de risco na propagação da cólera devido a escassez de recursos, o inadequado abastecimento de água, em quantidade e qualidade, pode ter contribuído na propagação da cólera em Moçambique, fato também encontrado durante a epidemia no Peru, nos anos 1991 e 1992, a qual teve uma forte relação com a falta de tratamento de água canalizada e fontes de água contaminadas 7,9,10 .…”
Section: Discussionunclassified